Human Intestinal Epithelial Cells Release Antiviral Factors That Inhibit HIV Infection of Macrophages - Guo, Le; Xu, Xi-Qiu; Zhou, Li; Zhou, Run-Hong; Wang, Xu; Li, Jie-Liang; Liu, Jin-Biao; Liu, Hang; Zhang, Biao; Ho, Wen-Zhe (Frontiers in Immunology, 2018)
As a rich source of CD4+ T cells and macrophages, the gastrointestinal (GI) tract is a major target site for HIV infection. The interplay between GI resident macrophages and intestinal epithelial cells (IECs) constitutes an important element of GI innate immunity against pathogens. In this study, we investigated whether human IECs have the ability to produce antiviral factors that can inhibit HIV infection of macrophages. We demonstrated that IECs possess functional toll-like receptor 3 (TLR3), the activation of which resulted in induction of key IFN regulatory factors (IRF3 and IRF7), IFN-β, IFN-λ and CC chemokines (MIP-1α, MIP-1β, RANTES), the ligands of HIV entry co-receptor CCR5. In addition, TLR3-activated IECs release exosomes that contained the anti-HIV factors, including IFN stimulated genes (ISGs: ISG15, ISG56, MxB, OAS-1, GBP5, and Viperin) and HIV restriction miRNAs (miRNA-17, miRNA-20, miRNA-28, miRNA-29 family members and miRNA-125b). Importantly, treatment of macrophages with supernatant (SN) from the activated IEC cultures inhibited HIV replication. Further studies showed that IEC SN could also induce the expression of antiviral ISGs and cellular HIV restriction factors (Tetherin and APOBEC3G/3F) in HIV-infected macrophages. These findings indicated that IECs might act as an important element in GI innate immunity against HIV infection/replication.